Heart failure hospitalizations and costs in ICD/CRT‐D recipients following replacement or upgrade: the DECODE registry. (4th September 2020) - Zacà, Valerio; Narducci, Maria Lucia; Ziacchi, Matteo; Valente, Serafina; Pelargonio, Gemma; Tomasi, Corrado; Bandini, Alberto; Zingarini, Gianluca; Calzolari, Vittorio; Del Rosso, Attilio; Boggian, Giulio; Sabbatani, Paolo; et al.
Abstract: Aims: The aim of this study is to report heart failure hospitalization (HFH) rates and associated costs within 12 months following implantable cardioverter defibrillator (ICD)/cardiac resynchronization therapy defibrillator (CRT‐D) device replacement or upgrade from ICD to CRT‐D. Methods and results: The DEtect long‐term COmplications after icD rEplacement (DECODE) was a prospective, single‐arm, multicentre cohort study that explored complications in ICD/CRT‐D recipients. All clinical and survival data at 12 months were prospectively analysed. For each adjudicated HFH, admission and discharge dates and ICD‐9‐CM diagnosis and procedure codes were recorded. The reimbursement for each HFH was calculated for each diagnosis‐related group code. Between 2013 and 2015, 983 patients (mean age 71 years, male 76%, mean left ventricular ejection fraction 35%, and New York Heart Association Class I/II 75.6%) were enrolled. Patients underwent device replacement (900; 91.6%, 446 ICD/454 CRT‐D) or ICD upgrade to CRT‐D (83; 8.4%). Post‐replacement hospitalizations occurred in 220 patients, with the primary discharge diagnosis identifying cardiovascular causes in 175 patients (80%). Fifty‐five (5.6%) patients experienced at least one HFH. Overall, 91 HFH events occurred (9.6% event rate, 95% confidence interval: 7.7–11.7) in 70 patients; 66 (6.7%) patients died, 40 (60.6%) of cardiovascular causes. The HFH rate was significantly higher following upgrades, and the occurrence of HFH was associated with an 11‐fold increased mortality risk (95% confidence interval: 5.9–20.5, P < 0.0001). Medical diagnosis‐related group accounted for 91.2% of HFH; the mean cost per HFH was €5662 ± 9497, and the mean cost per patient was €9369 ± 12 687. On multivariate analysis, predictors of HFH were atrial fibrillation, chronic kidney disease, and all‐cause hospitalization within 30 days prior to the procedure. Conclusions: In the DECODE registry, HFH and mortality rates in the year following ICD/CRT‐D replacement or upgrade were low. In this particular subset, underlying cardiac disease was the main driver of HFH, mortality, and higher healthcare expenditures.